Implications of Changes in the Role of Mamak on the Legitimacy of Minangkabau Customary Marriages: A Socio-Legal Study in Rantau and Ranah - Irma Fatmawati; Rahul Ardian; Annisa Febrina (CERED Indonesia Institute, 2025)
This study aims to analyze the implications of changes in the role of the 'mamak' on the validity of Minangkabau customary marriages, particularly by comparing practices in the 'ranah' (hometown) and in the 'rantau' (diaspora). In the Minangkabau matrilineal kinship system, the mamak holds a central position as clan leader, decision-maker, and the party that provides customary legitimacy for marriages. However, modernization, social mobility, and changes in family structure have led to shifts in the function and authority of the mamak in various social contexts. This study uses a socio-legal approach to examine how customary norms, religious law, and state law interact in the marriage process, while also exploring how society perceives the validity of marriage when the role of the mamak is no longer dominant. The results show that in the ranah, the role of the mamak remains relatively strong, so the validity of marriage is greatly influenced by the mamak's approval and presence in the customary proceedings. Meanwhile, in the regions, the authority of the mamak (maternal uncle) tends to decline and is often replaced by the biological father, religious figures, or other family figures, without affecting the validity of marriages according to state and religious law. This shift leads to variations in customary practices, potential family conflicts, and renegotiations of the meaning of 'valid' according to adat. Furthermore, it was found that communities make adjustments by recognizing the flexibility of adat as long as it does not conflict with sharia principles, allowing adat to continue in a changing social context. This study concludes that the changing role of the mamak has implications for the transformation of Minangkabau customary marriage practices but does not undermine the legitimacy of marriage as long as the principle of harmonization between adat, sharia, and positive law is maintained. These findings contribute to the development of customary law studies, the strengthening of the socio-legal basis in marriage studies, as well as the understanding of social change dynamics in matrilineal societies.